Finite element simulation for rock salt with dilatancy boundary coupled to fluid permeation - Mahnken, Rolf; Kohlmeier, M. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Parameter identification of gradient enhanced damage models with the finite element method - Mahnken, Rolf; Kuhl, Ellen (European Journal of Mechanics - A/Solids)
Keywords: General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; General Materials Science

A unified approach for parameter identification of inelastic material models in the frame of the finite element method - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Parameter identification for finite deformation elasto-plasticity in principal directions - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Determination of orientational distributions from 2H NMR data by a regularization method - Winterhalter, J.; Maier, D.; Grabowski, D. A.; Honerkamp, J.; Müller, S.; Schmidt, Claudia (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Optical storage effect in a platinum orthometalated liquid crystal - Buey, J.; Díez, L.; Espinet, P.; Kitzerow, Heinz-Siegfried; Miguel, J.A. (Applied Physics B: Lasers and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Bistable Diffractive Electro-Optical Effect in Cholesteric Gels* - Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
The present study shows that a cholesteric gel consisting of a low molar mass liquid crystal and a highly crosslinked anisotropic network can be switched between a transparent and a colored scattering state. The latter state can be induced in an initially non-aligned cholesteric liquid crystal by an electric field, as described recently by Chilaya and coworkers. A short pulse of an electric field can be used to select between the two states which are stable at zero field. The angular dependence of the wavelength of the diffracted light is studied in detail and explained by the known properties of the spatially periodic cholesteric structure.
Keywords: General Physics and Astronomy; General Engineering

Transient Light Scattering of a Ferroelectric and an Antiferroelectric Liquid Crystal with Short Pitch - Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
The electrooptic properties due to the transient light scattering mode (TSM) are studied for non-aligned ferroelectric and antiferro-electric liquid crystals with short pitch. The transient light scattering appears in thick samples without polarizers if the sign of an applied dc field is reversed. As a consequence, an ac field of suitable frequency can be used to switch the sample from a transparent to a scattering state. Due to the short pitch, a colored scattering can be observed under oblique angles. The latter effect provides high contrast ratios.
Keywords: General Physics and Astronomy; General Engineering

Storage of laser-induced holographic gratings in discotic liquid crystals - Contzen, J.; Heppke, G.; Kitzerow, Heinz-Siegfried; Krüerke, D.; Schmid, H. (Applied Physics B Laser and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Azimuthal Anchoring Energy in Photoinduced Anisotropic Films - Vorflusev, Valery P.; Kitzerow, Heinz-Siegfried; Chigrinov, Vladimir G. (Japanese Journal of Applied Physics)
Most electrooptic effects in liquid crystals require a uniform orientation of the director at the glass substrates. A new method to produce suitable alignment layers is based on the creation of anisotropic polymer films by photopolymerization with linearly polarized light. In the present paper we report on measurements of the anchoring strength of these photo-induced anisotropic films. Using a wedge-cell technique, we find an azimuthal anchoring energy of W ϕ ≈2.3·10 -6 J/m 2 .
Keywords: General Physics and Astronomy; General Engineering

Bistability in polymer‐dispersed ferroelectric liquid crystals - Molsen, Henning; Kitzerow, Heinz-Siegfried (Journal of Applied Physics)
Keywords: General Physics and Astronomy

A New Method to Align Smectic Liquid Crystals by Photo-Polymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
A novel technique to produce planar and homeotropic alignment of smectic liquid crystals is presented. The technique is based on producing an anisotropic polymer network in the bulk by photo-polymerizing a mixture of photoresist material and liquid crystal by linearly polarized UV-light. Both uniform planar alignment and homeotropic alignment can be obtained depending on the curing conditions. In the case of planar alignment, the orientation of liquid crystal molecules is governed by the direction of the polarization vector of the UV-light, thus making it possible to produce a defined azimuthal orientation of the liquid crystal director. This technique obviates the need to give any previous treatment to the bounding substrates.
Keywords: General Physics and Astronomy; General Engineering

Antiferroelectric Switching in Polymer-Dispersed Liquid Crystals - Molsen, Henning; Kitzerow, Heinz-Siegfried; Heppke, Gerd (Japanese Journal of Applied Physics)
We investigated the switching behavior of the well-known antiferroelectric liquid crystal (R)-4-(1-methylheptyloxycarbonyl)phenyl-4'-octyloxybiphenyl-4-carboxylate (MHPOBC), embedded in a polymer matrix. The alignment of the liquid crystal in the UV-cured adhesive was controlled by mechanical shear during the polymerization-induced phase separation. Multistable switching with time constants down to 150 µs indicates that antiferroelectric PDLC devices are promissing for electrooptic application as flexible displays.
Keywords: General Physics and Astronomy; General Engineering

Line shapes of field-induced blue-phase-III selective reflections - Kitzerow, Heinz-Siegfried; Crooker, P.; Heppke, G. (Physical Review Letters)
Keywords: General Physics and Astronomy

Dynamics of molecular reorientations: direct determination of rotational angles from two-dimensional NMR of powders - Schmidt, Claudia; Wefing, S.; Blümich, B.; Spiess, H.W. (Chemical Physics Letters)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy